Acetylation of ezrin regulates membrane–cytoskeleton interaction underlying CCL18-elicited cell migration. (22nd October 2019) - Song, Xiaoyu; Wang, Wanjuan; Wang, Haowei; Yuan, Xiao; Yang, Fengrui; Zhao, Lingli; Mullen, McKay; Du, Shihao; Zohbi, Najdat; Muthusamy, Saravanakumar; Cao, Yalei; Jiang, Jiying; et al.
Abstract: Ezrin, a membrane–cytoskeleton linker protein, plays an essential role in cell polarity establishment, cell migration, and division. Recent studies show that ezrin phosphorylation regulates breast cancer metastasis by promoting cancer cell survivor and promotes intrahepatic metastasis via cell migration. However, it was less characterized whether there are additional post-translational modifications and/or post-translational crosstalks on ezrin underlying context-dependent breast cancer cell migration and invasion. Here we show that ezrin is acetylated by p300/CBP-associated factor (PCAF) in breast cancer cells in response to CCL18 stimulation. Ezrin physically interacts with PCAF and is a cognate substrate of PCAF. The acetylation site of ezrin was mapped by mass spectrometric analyses, and dynamic acetylation of ezrin is essential for CCL18-induced breast cancer cell migration and invasion. Mechanistically, the acetylation reduced the lipid-binding activity of ezrin to ensure a robust and dynamic cycling between the plasma membrane and cytosol in response to CCL18 stimulation. Biochemical analyses show that ezrin acetylation prevents the phosphorylation of Thr567. Using atomic force microscopic measurements, our study revealed that acetylation of ezrin induced its unfolding into a dominant structure, which prevents ezrin phosphorylation at Thr567. Thus, these results present a previously undefined mechanism by which CCL18-elicited crosstalks between the acetylation and phosphorylation on ezrin control breast cancer cell migration and invasion. This suggests that targeting PCAF signaling could be a potential therapeutic strategy for combating hyperactive ezrin-driven cancer progression.